Designing and Improving a Blended Synchronous Learning Environment: An Educational Design Research - Wang, Qiyun; Quek, Choon Lang; Hu, Xiaoyong (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
In this study, a blended synchronous learning environment (BSLE) was created to support a group of graduate students when they were taking a course. Instruction was delivered to both face-to-face (F2F) and online students simultaneously. The purpose of this paper is to present how this BSLE was gradually designed, implemented, and improved by following the educational design research approach. Results showed that the BSLE environment had the capability to support online and classroom students at the same time and provide equivalent learning experiences for them, but challenges emerged in the process. Design principles were summarized to guide researchers or teachers when they design similar learning environments.